Friction-Spinning – Possibility of Grain Structure Adjustment. (2017) - Lossen, Benjamin; Andreiev, Anatolii; Homberg, Werner; Schaper, Mirko
Abstract: The friction spinning process is an innovative incremental forming technique that enables high degree forming operations in the field of tube and sheet metal forming. The integration of friction-sub-processes from friction welding into a metal spinning process permits the self-induced heat generation of the part. Compared with conventional spinning processes, this in-process heat treatment allows the extension of existing forming limits and also the production of more complex geometries from tubes and sheets. Additionally, the material/part properties like hardness, stress, grain structure/orientation, surface conditions etc. can be adjusted in a defined way during the forming process. This can be achieved through the use of appropriate process parameter settings in combination with the degree of deformation. The choice of feed rate, relative motion and friction coefficient gives rise to a defined temperature profile and allows the use of specific process control strategies to produce parts with different material properties in different areas. Thus, the production of a new class of individually adjustable components is enabled. For example, these parts could be designed for load optimized applications like complex hollow parts in aluminium or steel. This paper presents the results of the grain structure investigations and clarifies the influence of different process parameters in aluminium tube processing especially during flange forming operations. A flange will thus be formed from an aluminium tube and, using to further tool systems, the wall thickness of the flange can be adjusted in a defined manner. The paper addresses the influence of the significant process parameters (feed rate, rotation speed, temperature, wall thickness reduction and forming time) on the grain structure refine-ment during flange forming. In addition, the impact of the material properties (hardness, stress/strain behaviour) will be considered.